2011
DOI: 10.1007/s11258-011-9924-0
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment dynamics of two low-density neotropical multiple-use tree species

Abstract: In the present study, we describe the temporal and spatial variability in recruitment, growth, and mortality rates of seedlings and saplings of two low-density neotropical tree species, Dipteryx odorata and Copaifera reticulata in Eastern Amazonia, Brazil. As both species have important timber and non-timber uses, for each species we compare regeneration parameters among different management scenarios (sites used for timber logging, nontimber product extraction, and undisturbed forests). Results suggest that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
0
17
0
7
Order By: Relevance
“…These heavy fruiting events are frequent in tropical forests (de Steven, 1994;Norden et al, 2007), and include the two species studied (Herrero-Jáuregui et al, 2011). Based on the results of this study and those published by Herrero-Jáuregui et al (2011), it is reasonable to attribute light-demanding characteristics to these two species, which has major implications for their sustainable management. The comparison of the diameter structure in the different management situations studied can shed some light on the impacts of management, particularly in the case of D. odorata.…”
Section: Discussionmentioning
confidence: 58%
“…These heavy fruiting events are frequent in tropical forests (de Steven, 1994;Norden et al, 2007), and include the two species studied (Herrero-Jáuregui et al, 2011). Based on the results of this study and those published by Herrero-Jáuregui et al (2011), it is reasonable to attribute light-demanding characteristics to these two species, which has major implications for their sustainable management. The comparison of the diameter structure in the different management situations studied can shed some light on the impacts of management, particularly in the case of D. odorata.…”
Section: Discussionmentioning
confidence: 58%
“…Despite an increase in recruitment rate of D. odorata in the first year after harvesting, RIL did not affect its density. Herrero-Jáuregui et al (2011), in the same national forest, found no effects of logging on the recruitment of D. odorata. Although low numbers of individuals, H. courbaril increased its density in the logged areas by year six after logging.…”
Section: Densitymentioning
confidence: 80%
“…In tropical forests, regeneration may depend on natural disturbances (Fredericksen and Putz, 2003). Disturbances caused by logging may affect regeneration of valuable tree species in different ways (Gómez, 2011;Herrero-Jáuregui et al, 2011). Canopy opening increases the density and growth rates of both light-demanding (Nabe-Nielsen et al, 2007) as well as shade-tolerant species (Toledo-Aceves et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This three-year figure has already been given by empirical studies (Leite et al, 2001 andPinto et al, 2010), although Newton et al (2011) disagree with this minimum interval between successive extractions. Some papers do suggest longer cycles (e.g., 8 years in Herrero-Jáuregui et al, 2011). In summary, no consensus exists in the literature on the optimal cycle of copaíba oleoresin harvesting.…”
Section: Discussionmentioning
confidence: 98%
“…Also unknown is how much oleoresin can be removed without causing damage to the wider ecological and physiological processes surrounding this species, which management factors influence production, (Plowden, 2003(Plowden, , 2004Medeiros and Vieira, 2008) and the level that can be extracted sustainably. Some researchers (Herrero-Jáuregui et al, 2011) argue that the extraction of copaíba oleoresin does not affect the regeneration of the species.…”
Section: Introductionmentioning
confidence: 99%